Stability and Performance of Conventional and Sharia Banking in Indonesia Before and After the Covid-19 Pandemic - Eko Nugroho, Taufik; Hendranastiti, Nur Dhani (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This study examines the impact of the COVID-19 outbreak on the performance and stability of Indonesia's dual banking system. Our sample includes the top 20 banks by assets, both conventional and sharia, from 2018 Q1 to 2023 Q3. Data for conventional banks is obtained from Bloomberg, while data for Islamic banks is sourced from each bank's official website. We use ROA, ROE, and NIM as performance variables and Z-Score and NPL as stability variables. External factors such as GDP, Inflation, BI Rate, and Exchange Rate serve as independent variables, while bank-specific variables act as controls. Panel data regression is used to determine causal relationships between these factors and banking performance and stability. We also compare bank performance and stability before and after COVID-19 using the Mann-Whitney Test. Findings indicate that the pandemic significantly affected conventional banks' Z-Score, NPL, ROA, ROE, and NIM, while only NPL was significantly affected in sharia banks. The results highlight the significant impact of GDP, exchange rate, and BI Rate on banking variables, while inflation had no effect. The type of bank significantly influences performance but not stability.